DNA polymerase Gp90 activities and regulations on strand displacement DNA synthesis revealed at single‐molecule level. Issue 5 (28th April 2021) - Zhang, Shuming; Xiao, Xue; Kong, Jingwei; Lu, Ke; Dou, Shuo‐Xing; Wang, Peng‐Ye; Ma, Lu; Liu, Yuru; Li, Guohong; Li, Wei; Zhang, Huidong
Abstract: Strand displacement DNA synthesis (SDDS) is an essential step in DNA replication. With magnetic tweezers, we investigated SDDS kinetics of wild‐type gp90 and its exonuclease‐deficient polymerase gp90 exo ‐ at single‐molecule level. A novel binding state of gp90 to the fork flap was confirmed prior to SDDS, suggesting an intermediate in the initiation of SDDS. The rate and processivity of SDDS by gp90 exo ‐ or wt‐gp90 are increased with force and dNTP concentration. The rate and processivity of exonuclease by wt‐gp90 are decreased with force. High GC content decreases SDDS and exonuclease processivity but increases exonuclease rate for wt‐gp90. The high force and dNTP concentration and low GC content facilitate the successive SDDS but retard the successive exonuclease for wt‐gp90. Furthermore, increasing GC content accelerates the transition from SDDS or exonuclease to exonuclease. This work reveals the kinetics of SDDS in detail and offers a broader cognition on the regulation of various factors on SDDS at single‐polymerase level.